Breakfast of champions, or, Goodbye blue Monday! - Vonnegut, Kurt. (New York : Delacorta Press, 2006)
The author questions the condition of modern man in this novel depicting a science fiction writer's struggle to find peace and sanity in the world.
930
Keywords: Science fiction -- Authorship; Trout, Kilgore (Fictitious character) -- Fiction; Sex -- Fiction; Mental illness -- Fiction; Satire; Humorous fiction